Hydrodynamic Properties of Tris(2-methylbutyl) Phosphate and Tri-n-alkyl Phosphates in n-Dodecane – A Comparative Investigation between Unirradiated and Gamma Irradiated Solvent Systems. Issue 5 (29th July 2022) - Sarkar, Subramee; Rajeswari, S.; Suresh, A.; Sivaraman, N.
ABSTRACT: The physicochemical parameters of tris(2-methylbutyl) phosphate (T2MBP), a molecule possessing the essential characteristics required to be considered as a promising extractant in the solvent extraction stage of fast reactor fuel reprocessing, have been evaluated in the present study. In this context, the density, viscosity and interfacial tension (IFT), which are considered to be few among the important solvent selection criteria prior to its deployment in the plant scale have been measured for T2MBP in n -dodecane ( n -DD) based systems. Similar studies have been performed with its straight chain isomer, tri- n -amyl phosphate (TAP) as well as the widely utilized commercial extractant, tri- n -butyl phosphate (TBP) so as to emphasize on the structural effects. Though the trends on the physicochemical behaviour of TBP based systems (temperature and ligand concentration effects) are well known in the literature, the data on TBP have been generated in the present work for comparison with the T2MBP results under similar experimental conditions. Solutions of trialkyl phosphates (TalP) in n -DD of different concentrations have been used to generate the data on the variation of density, IFT and viscosity with the change in the ligand concentration. In addition, the transformation in their properties has been assessed after subjecting the solvents to various levels of gamma absorbed doses. Overall, it has been observed that there was no significant variation in the density of the irradiated TalPs; however, there was a significant rise in the viscosity and reduction in the IFT of the TalP samples upon irradiation. The data on the Gibbs energy change of activation of various 1.1 M TalP/ n -DD solutions have been generated by fitting their respective dynamic viscosity value as a function of temperature using Andrade's equation. Moreover, from the IFT value, the parameters relating to the interfacial activity of TalP/ n -DD solutions have been determined using the Szyszkowski adsorption isotherm.